Emerging model villages in India : a study of Punsari village from the state of Gujarat (India) - Joshi, Sanhita Rahul (Array, 2019)
Although India no more lives in its villages, the rural population is still sizeable and, more importantly, it reels under the pressure of extreme poverty, pitiable basic amenities, and dearth of livelihood opportunities. Urbanisation and urban growth has captured the attention of government and policy makers especially in the post liberalisation period. However, much needs to be done to improve the conditions of the people living in rural areas. Strengthening of village democracywas considered as a possible solution to resolving issues at the grass-roots level. This paved way for the historic 73rd Constitutional Amendment Act (CAA) in 1993 which sought to empower people at the base of India’s federal polity. Encouraging people’s participation in the process of development, policy making and its implementation was the fundamental objective of this legislation. Twenty- five years have passed since the adoption of the 73rd CAA in 1993 but still much needs to be done. There is an urgent need to transform the rural landscape of India and bring it on a par with its urban counterparts while retaining thesoul of rural life. The case of village Punsari from the Sabharkantha District of the state of Gujarat (India) is unique as it stands out as a smart and model village. All the modern amenities found in an urban area are available in this village. Using descriptive analytical framework, the paper aims to argue that such smart villages are a ray of hope for the rural revitalisation in Indian countryside. Semi-structured interviews with the local leaders, officers, and stakeholders form an important part of the research used to generate insights and conclusions. Thepaper argues that grass-roots leadership, community participation, decentralisation of powers to local bodies in rural areas, and financial support in the form of various government schemes can bring far-reaching changes in the rural landscape of India.